Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Pemoderasi - Verawaty, Verawaty; Nespy, Reza (Universitas Muhammadiyah Metro, 2022)
This study aims to examine the effect of the audit committee, independentcommissioners, board of directors, managerial ownership and capital structure on firmvalue with profitability as a moderating variable in food and beverage companies listedon the Indonesia Stock Exchange. The research was quantitative. The sample in thisstudy was obtained using the purposive sampling method which resulted in a sample of36 samples from 12 manufacturing companies in the food and beverages sector listedon the Indonesia Stock Exchange during the 2018-2020 period. The analysis techniqueused is multiple linear regression analysis with the Moderated Regression Analysis(MRA) method. The research result concluded that audit committee had an effect onfirm value, while independent commissioners, board director, managerial ownershipand capital structure had no effect on firm value. audit committee, board director andcapital structure have an effect on firm value moderated by profitability, whileindependent commissioners and managerial ownership did not affect firm value eventhough it has been moderated by profitability